Motivation through indirect compensation: Evaluating employee performance in Enugu State Civil Service Commission - Udodiugwu, Michael Ikenna; Nwosu, Chibuzo Charles; Obiakor, Ugochukwu Jude; Nwumeh, Uchenna Juliana (Goodwood Publishing, 2024)
Purpose: This study evaluates the impact of indirect compensation on employee job performance by the Enugu State Civil Service Commission. Research Methodology: This study employed a cross-sectional survey research design with a population of 280 participants, comprising staff from the Administration, Planning and Budgeting, and Research & Statistics Units, spanning grade levels 2-16 within the Enugu State Civil Service Commission. Data were collected using a questionnaire as the primary tool and rigorously analyzed using the Pearson correlation coefficient in the Statistical Package for Social Sciences (SPSS) version 23. Results: The findings revealed a significant positive impact of indirect compensation metrics on employee performance of the Enugu State Civil Service Commission. Limitations: The study specifically targeted personnel within grade levels 2-16 of the Enugu State Civil Service Commission. Contribution: This research significantly advances our understanding of indirect compensation and its impact on employee performance by pioneering new concepts, refining existing theories, and conducting comprehensive empirical studies. Funding: This research did not receive any funding from any Agency or Organization.